Inovasi Desain Dan Produksi Kain Lurik Pedan Untuk Memenuhi Kebutuhan Accessoris Perhotelan - Siti Badriyah; Muh Arif Jati Purnomo; Joko Budiwiyanto; Ahmad Fajar Ariyanto; Amina Sukma Dewi; Sartiyasto (LP2MP3M, INSTITUT SENI INDONESIA SURAKARTA, 2019)
Potential uniqueness of Lurik Pedan fabric not only distributed as textile but it can be optimally used using development of accessories design innovation and hotel accessories as strategic marketing which become the core in this activity. Some handicraft industry in Klaten (woodcraft, foundry industry, earthenware industry, and interior accessories) are worked together to maximize the goal. Training, mentoring, redesign, procurement of equipment and supplies, and product expo are implemented to achieve the goal. Training such as design, accessories product, hotel accessories, redesign (lay out of workshop and showroom area, facade, fireplace, interior sign, dyeing yarn tub, lighting, and corporate identity); procurement of appropriate technology for example thread scouring furnace, handloom, thread dryer tool, and exhibition display tools. Those activities will be allocated in three years based on the urgency which is synchronized with performance production of SMEs (Small and Medium Enterprises) are plotted in schedule master that has been previously agreed.